Cataract: the relation between myopia and cataract morphology. Issue 6 (June 1987) - Brown, N A; Hill, A R
Abstract : The association between high myopia and cataract is already well established and an association between simple myopia and cataract has been suggested, but it has not been clear to what extent the myopia precedes the cataract or is the result of it. The present study compares the refraction of a group of 100 British patients at the time of first presentation with cataract in whom the refraction was also known four years previously, with a group of matched controls in whom the refraction was also known four years previous to presentation. The study shows that simple myopia does not appear to predispose to cataract. It is the development of the cataract itself, in particular nuclear sclerosis, which causes the refractive change towards myopia. The myopic change precedes the development of cataract, and patients over the age of 55 showing a myopic change in refraction have a very high probability of developing nuclear sclerotic cataract. The healthy aging eye and eyes with cortical cataract or subcapsular cataract, but without nuclear sclerosis, continue to show a gradual hypermetropic change with time.